2012
DOI: 10.1016/j.bbadis.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Functions of plasmalogen lipids in health and disease

Abstract: Plasmalogens are a unique class of membrane glycerophospholipids containing a fatty alcohol with a vinyl-ether bond at the sn-1 position, and enriched in polyunsaturated fatty acids at the sn-2 position of the glycerol backbone. These two features provide novel properties to these compounds. Although plasmalogens represent up to 20% of the total phospholipid mass in humans their physiological roles have been challenging to identify, and are likely to be particular to different tissues, metabolic processes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
922
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 864 publications
(958 citation statements)
references
References 115 publications
26
922
2
8
Order By: Relevance
“…This is in agreement with the current knowledge about plasmalogen distribution and function since they are known to be abundant in gray matter where they play an active metabolic role [8,24]. We were particularly interested in the latencies of evoked potentials as a reflection of myelination, since in humans plasmalogens constitute the majority of total phospholipids in the white matter and signal abnormalities on MRI are present in patients with the severe, but not the milder phenotype of RCDP [6,8]. We found that 93% of VEP latencies were initially normal for age and that deterioration occurred in 31% of patients with both the severe and mild phenotype.…”
Section: Discussionsupporting
confidence: 75%
“…This is in agreement with the current knowledge about plasmalogen distribution and function since they are known to be abundant in gray matter where they play an active metabolic role [8,24]. We were particularly interested in the latencies of evoked potentials as a reflection of myelination, since in humans plasmalogens constitute the majority of total phospholipids in the white matter and signal abnormalities on MRI are present in patients with the severe, but not the milder phenotype of RCDP [6,8]. We found that 93% of VEP latencies were initially normal for age and that deterioration occurred in 31% of patients with both the severe and mild phenotype.…”
Section: Discussionsupporting
confidence: 75%
“…90 Plasmalogens are a class of glycerophospholipids with anti-oxidative properties that are present in HDL only in low amounts. 78,[97][98][99] Patients with CAD had HDL relatively depleted of the plasmalogen species PC33:3, PC35:2 and PC34:2 and with a compromised ability to inhibit apoptosis of endothelial cells. 89 The finding that incorporation of the plasmalogen PC35:2 in rHDL improved its anti-apoptotic activity towards endothelial cells further underscored the potential importance of plasmalogens for the anti-apoptotic activity of HDL.…”
Section: Glycerophospholipidsmentioning
confidence: 99%
“…It has been suggested that serum plasmalogen levels are associated with diverse clinical manifestations 1 . Recently, particular attention has been paid to the involvement of plasmalogens in metabolic diseases associated with oxidative stress and chronic inflammation 2 6 .…”
Section: Introductionmentioning
confidence: 99%